Examining preservice mathematics teachers’ basic teaching skills in technology-integrated microteaching - Effendi, Moh. Mahfud; Ummah, Siti Khoiruli; Andriyani (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
The background of this research is based on previous studies that emphasize the importance of mastering basic teaching skills for prospective teachers to support effective learning. The purpose of this study was to explore undergraduate students’ basic teaching skills in managing mathematics classes through microteaching activities. This study employed a case study method involving 29 undergraduate preservice teachers from the second cohort of the Mathematics Education Study Program. Data were analyzed through triangulation of primary literature on teaching skills, classroom observations, and microteaching document studies. The reconstruction of the Outcome Based Education (OBE) curriculum produced a course titled Innovative Learning Design, which includes outputs in the form of learning tools, microteaching sessions, and microteaching videos. The findings revealed that all basic teaching skills were performed satisfactorily. The most prominent skills were opening and closing lessons and using technology-integrated media. In contrast, the least evident skills were explaining and providing reinforcement, as some preservice teachers had not yet mastered prerequisite or fundamental mathematics concept. Based on these findings, it is recommended that future research analyze the influence of basic teaching skills on student learning outcomes and active student engagement in class.